A comparison of F waves in peripheral nerve disorders - (:unkn) unknown (My University, 2005)
Background and aim: F waves have become integral parts of nerve conduction studies in particular. F minimum (Fmin), the most commonly assessed latency, represents the largest and the fastest conducting fibers. The diagnostic yields of other F wave parameters are not obvious. In the present study, we aimed to determine the value of F wave parameters in commonly seen peripheral nerve disorders. Material and method: We studied the F responses in 118 patients who had been diagnosed with different types of neuropathies, clinically and electrodiagnostically, and 68 individuals were used as controls: A total of 470 motor nerve conduction studies and related F-wave parameters were analyzed. Discussion: F maximum (Fmax) was the most commonly seen abnormal parameter in the present study, although Fmin has until now been the most commonly studied parameter in clinics routinely. Abnormalities of F waves were more frequently seen in the patients compared to those in the controlgroup and the differences were significant for carpal tunnel syndrome and upper extremity radiculopathies. Conclusion: This large database showed that F wave evaluations should include not only Fmin but also Fmax.
Keywords: Carpal tunnel syndrome; F wave latency; Polyneuropathy; Radiculopathy